Miniatlas of Human Security - World Bank (Brighton, UK: Myriad Editions, 2016)
An at-a-glance illustrated guide to global and regional trends in human insecurity, the miniAtlas provides a succinct introduction to today's most pressing security challenges. It maps political violence, the links between poverty and conflict, assaults on human rights including the use of child soldiers and the causes of war and peace.